Sikap Lanjut Usia Tentang Perubahan Fisiologis Dari Aktifitas Seksual Di Desa Wonokalang Wonoayu Sidoarjo - Priyantini; Dwiharini Puspitaningsih (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Aging Process (Aging) is a natural process that accompanied the decline of their physical, psychological and social interact with each other. One problem that often in the elderly complain about the changes of sexual activity. Therefore this study was conducted to determine attitudes about the elderly physiological changes of sexual activity. This reseach uses descriptive study design with a total population of 46 people aged 60-70 years old, the sample totaled 41 respondents using probability sampling technique type cluster random sampling, the instrument used a structured questionnaire through interviews. The variables in the elderly is the attitude about the precise physiological changes of sexual activity, after data analysis of data obtained using the formula T score. The results showed that more than 50% of respondents being negative towards the physiological changes of sexual activity were 21 as many respondents (51.2%). Negative attitudes of respondents toward the physiological changes of sexual actifity is because that according to their desires and their penggairahan of sexual actifity is still the same as when ayoung man, nothing has changed. It is expected that the elderly can comprehend and understand that in old age that there are some changes among the psyiological changes of sexual actifity that involved several steps that desire phase, the phase of araosol, orgasmic phase, post orgasmic phase. In order not to adversely affect both physically and psychologically from the elderly can make healthy sexual actifity, desired and can be enjoyed together.